Pelatihan Merancang dan Mengembangkan Multimedia Pembelajaran untuk Guru di SD Negeri Bajangan Kabupaten Pasuruan - Ardiansyah, Arief; Asfiyak, Khoirul (Amalee: Indonesian Journal of Community Research and Engagement, 2020)
Multimedia learning has been widely used as a medium of learning in the classroom as its effectiveness in improving student learning outcomes. However, there are still many schools unable to develop and implement it, due to the lack of knowledge and skills of teachers in developing it, the unavailability of means to implement it, and the absence of special training to develop it. This program aims to provide training in designing and developing interactive learning multimedia for teachers at Bajangan Elementary School, Pasuruan Regency. Using the guided tutorial method which is directly guided by an expert trainer, found that the final result of the training is that the teachers are able to develop multimedia interactive learning independently in accordance with the characteristics of their field of study. The evaluation process, by visiting the school one week after the training activities and by looking at multimedia learning programs, shows that the program has been successfully developed by the teachers. Keywords: development, instructional multimedia, teacher, training. Abstrak Pembelajaran multimedia telah banyak digunakan sebagai media pembelajaran di kelas karena efektivitasnya dalam meningkatkan hasil belajar siswa. Namun, masih banyak sekolah yang tidak dapat mengembangkan dan mengimplementasikannya, karena kurangnya pengetahuan dan keterampilan guru, tidak tersedianya sarana, dan tidak adanya pelatihan khusus untuk mengembangkannya. Program ini bertujuan untuk memberikan pelatihan dalam merancang dan mengembangkan multimedia pembelajaran interaktif untuk para guru di Sekolah Dasar Bajangan, Kabupaten Pasuruan. Menggunakan metode tutorial terbimbing yang dipandu langsung oleh pelatih ahli, didapati bahwa melalui pelatihan ini para guru dapat mengembangkan pembelajaran interaktif multimedia secara mandiri sesuai dengan karakteristik bidang studi mereka. Proses evaluasi, dengan mengunjungi sekolah satu minggu setelah kegiatan pelatihan dan dengan melihat program pembelajaran multimedia, menunjukkan bahwa program tersebut telah berhasil dikembangkan oleh para guru. Kata Kunci: guru, multimedia pembelajaran, pelatihan, pengembangan.